ความต้องการจำเป็นในการพัฒนาทรัพยากรมนุษย์ของโรงเรียนขจรโรจน์วิทยา - ภาณุรัตน์, สุทธาวรรณ; ศิริภิรมย์, วลัยพร (An Online Journal of Education, 2018)
This research was conducted using a descriptive research method. The objectives of this research were 1) to study the actual state and the desirable state of human resource development of Khajornroajwitthaya School. 2) To study the priority needs of human resource development of Khajornroajwitthaya School. The population of this study consisted of 90 Khajornroajwitthaya School’s teachers. The research instrument used in this study was the 5 level rating scaled questionnaire. The data was analyzed by frequency distribution, percentage, mean, standard deviation, and PNI Modified. The finding indicate that 1) The actual state of HRD of Khajornroajwitthaya School in term of the overall and all of characteristic were practiced at a high level. Considering each characteristic, it was found that the highest mean score is Assess and Prioritize HRD Needs stage. The desirable state of HRD of Khajornroajwitthaya School in term of the overall and each characteristic was practiced at a high level. Considering each characteristic, it was found that the highest mean score is Assess and Prioritize HRD Needs stage. 2) The priority needs of in-school human resource development of Khajornroajwitthaya School found that the highest priority need index of human resource development is Design HRD Programs stage, followed by Assess and Prioritize HRD Needs stage and Implement HRD Programs stage, and the lowest priority needs index is the Evaluate HRD Programs stage.